Frequency of thyroid function tests and examinations in participants of a population-based study - Simone Kiel; Till Ittermann; Henry Völzke; Jean-François Chenot; Aniela Angelow (BMC, 2020)
Abstract Background Thyroid disorders are common in the adult German population. Little is known about guideline implementation in clinical practice and the prevalence of diagnostic procedures in ambulatory care. The study aims to investigate the use of thyroid hormone measurements, thyroid ultrasound, thyroid scintiscan and associated costs in ambulatory care at population level. Methods Data were derived from two independent population-based cohorts of the Study of Health In Pomerania (SHIP). Ambulatory billing data from the Association of Statutory Health Insurance Physicians Mecklenburg-Vorpommern were individually linked for the period 2002-2016 with SHIP data. The main outcomes were the frequency of outpatient ultrasound, scintiscan, serum TSH level measurement, free triiodothyronine (fT3) and free thyroxine (fT4) measurement, TSH-receptor-antibodies and microsomal antibodies measurement within 1 year and 3 years prior to the study entrance of the participants. Multinomial logistic regression models were used to assess the association of age, sex, thyroid medication intake and Charlson-Comorbidity-Index with frequency of TSH measurements and ultrasound examinations. Results A total of 5552 participants (47% male, median age 55) were included in the analysis. 25% (1409/5552) had a diagnosed thyroid disorder or treatment, 40% (2191/5552) had clinical findings based on ultrasound or laboratory testing in SHIP only and 35% (1952/5552) neither a coded thyroid disorder or clinical finding nor thyroid medication. In the total study population 30% (1626/5552) received at least one TSH measurement, 6.8% (378/5552) at least one thyroid ultrasound and 2.6% (146/5552) at least one scintiscan within the past year before the study examination. Tests were performed more frequently in patients with thyroid medication and coded thyroid disorders. Hence, this group caused the highest expenditures. Conclusions Given the high prevalence of thyroid disorders, diagnostic and monitoring tests should be used rationally with regard to costs. TSH levels should be monitored regularly in patients on thyroid medication. A consensus on monitoring frequency and iteration of monitoring of morphological thyroid disorders with TSH and ultrasound and specific guideline recommendations are needed. Trial registration Versorgungsforschung Deutschland (VfD_17_003880).